Galectin-9 as an indicator of functional limitations and radiographic joint damage in patients with rheumatoid arthritis - Guo, Jiewen; Ai, Xiaoyuan; Jia, Baixue; Zhong, Xiaoling; Liu, Lixiong; Hu, Qiu; Xie, Jingyi; Hong, Xiaoping; Chen, Yulan; Liu, Dongzhou (Frontiers in Immunology, 2024)
Background Previous studies have revealed that Galectin-9 (Gal-9) acts as an apoptosis modulator in autoimmunity and rheumatic inflammation. In the present study, we investigated the potential role of Gal-9 as a biomarker in patients with rheumatoid arthritis (RA), especially as an indicator of functional limitations and radiographic joint damage. Methods A total of 146 patients with RA and 52 age- and sex-matched healthy controls were included in this study. Clinical data including disease activity, physical function, and radiographic joint damage were assessed. Functional limitation was defined as the Stanford Health Assessment Questionnaire (HAQ) disability index >1. Subjects with joint erosion >0 or joint space narrowing >0 were considered to have radiographic joint damage. Serum Gal-9 levels were detected by an enzyme-linked immunosorbent assay. Univariate and multivariate logistic regression analysis were used to evaluate the association between Gal-9 and high disease activity and functional limitations, and a prediction model was established to construct predictive nomograms. Results Serum levels of Gal-9 were significantly increased in patients with RA compared to those in healthy controls (median 13.1 ng/mL vs. 7.6 ng/mL). Patients with RA who were older (>65 years), had a longer disease duration (>5 years), longer morning stiffness (>60mins), elevated serum erythrocyte sedimentation rate and C-reactive protein, and difficult-to-treat RA had significantly higher Gal-9 levels than those in the corresponding control subgroups (all p <0.05). Patients with RA were divided into two subgroups according to the cut-off value of Gal-9 of 11.6 ng/mL. Patients with RA with Gal-9 >11.6 ng/mL had a significantly higher core clinical disease activity index, HAQ scores, Sharp/van der Heijde modified Sharp scores, as well as a higher percentage of advanced joint damage (all p<0.05) than patients with Gal-9 ≤11.6 ng/mL. Accordingly, patients with RA presenting either functional limitations or radiographic joint damage had significantly higher serum Gal-9 levels than those without (both p <0.05). Furthermore, multivariate logistic regression analysis showed that a serum level of Gal-9 >11.6 ng/mL was an independent risk factor for high disease activity (OR=3.138, 95% CI 1.150–8.567, p=0.026) and presence of functional limitations (OR=2.455, 95% CI 1.017–5.926, p=0.046), respectively. Conclusion Gal-9 could be considered as a potential indicator in patients with RA, especially with respect to functional limitations and joint damage.